In vitro OP9-DL1 co-culture and subsequent maturation in the presence of IL-21 generates tumor antigen-specific T cells with a favorable less-differentiated phenotype and enhanced functionality - Sarah Bonte; Stijn de Munter; Lore Billiet; Glenn Goetgeluk; Joline Ingels; Hanne Jansen; Melissa Pille; Laurenz de Cock; Karin Weening; Tom Taghon; Georges Leclercq; Bart Vandekerckhove; et al. (OncoImmunology, 2021)
T cell receptor (TCR)-redirected T cells target intracellular antigens such as Wilms’ tumor 1 (WT1), a tumor-associated antigen overexpressed in several malignancies, including acute myeloid leukemia (AML). For both chimeric antigen receptor (CAR)- and TCR-redirected T cells, several clinical studies indicate that T cell subsets with a less-differentiated phenotype (e.g. stem cell memory T cells, TSCM) survive longer and mediate superior anti-tumor effects in vivo as opposed to more terminally differentiated T cells. Cytokines added during in vitro and ex vivo culture of T cells play an important role in driving the phenotype of T cells for adoptive transfer. Using the OP9-DL1 co-culture system, we have shown previously that we are able to generate in vitro, starting from clinically relevant stem cell sources, T cells with a single tumor antigen (TA)-specific TCR. This method circumvents possible TCR chain mispairing and unwanted toxicities that might occur when introducing a TA-specific TCR in peripheral blood lymphocytes. We now show that we are able to optimize our in vitro culture protocol, by adding IL-21 during maturation, resulting in generation of TA-specific T cells with a less-differentiated phenotype and enhanced in vitro anti-tumor effects. We believe the favorable TSCM-like phenotype of these in vitro generated T cells preludes superior in vivo persistence and anti-tumor efficacy. Therefore, these TA-specific T cells could be of use as a valuable new form of patient-tailored T cell immunotherapy for malignancies for which finding a suitable CAR-T target antigen is challenging, such as AML.